Original data matrix for "Plants as highly diverse sources of construction wood, handicrafts and fibre in the Heihe National Forest Park (Shaanxi, China)" - Łukasz, Łuczaj (My University, 2017)
Data matrix for the article "Plants as highly diverse sources of construction wood, handicrafts and fibre in the Heihe National Forest Park (Shaanxi, China)"
Keywords: ethnobotany; China